Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1e) Để \(\frac{2x-1}{x-3}\) nguyên thì \(2x-1⋮x-3\)
\(\Leftrightarrow2x-6+5⋮x-3\)
\(\Leftrightarrow2\left(x-3\right)+5⋮x-3\)
Do \(2\left(x-3\right)⋮x-3\) \(\Rightarrow5⋮x-3\)
\(\Rightarrow x-3\in\left\{-5;-1;1;5\right\}\)
\(\Leftrightarrow x\in\left\{-2;2;4;8\right\}\)
Vậy:...................
2: 12-10x=25-30x
=>20x=13
=>x=13/20
3: \(3\left(2x+3\right)-2\left(4x-5\right)=10x+21\)
=>6x+9-8x+10=10x+21
=>10x+21=-2x+19
=>12x=-2
=>x=-1/6
4: \(\Leftrightarrow25x-15-6x+12=11-5x\)
=>19x-3=11-5x
=>24x=14
=>x=7/12
5: \(\Leftrightarrow8-12x-5+10x=4-6x\)
=>4-6x=-2x+3
=>-4x=-1
=>x=1/4
6: \(\Leftrightarrow32x-24-6+9x=13-40x\)
=>41x-30=13-40x
=>81x=43
=>x=43/81
7: \(\Leftrightarrow10x-5+20x=5x-11\)
=>30x-5=5x-11
=>25x=-6
=>x=-6/25
a,45 + x = 2x e, 4x + 3x = 70
\(\Rightarrow2x-x=45\) \(\Rightarrow7x=70\)
\(\Rightarrow x=45\) \(\Rightarrow x=10\)
Vậy x = 45 Vậy x = 10
b, 2 + x - 4 = 12 f, 6x - 18 = 0
\(\Rightarrow2+x=12+4\) \(\Rightarrow6x=18\)
\(\Rightarrow2+x=16\) \(\Rightarrow x=3\)
\(\Rightarrow x=14\) Vậy x = 3
Vậy x = 14 g, 72x : 36 = 2
c, 10 + x = 5 + 2x \(\Rightarrow72x=72\)
\(\Rightarrow2x+x=10+5\) \(\Rightarrow x=1\)
\(\Rightarrow3x=15\) Vậy x = 1
\(\Rightarrow x=5\) h, 13 + x = 5 + 2x
Vậy x = 5 \(\Rightarrow2x+x=13+5\)
d, 42 - 2x = 12 \(\Rightarrow3x=18\)
\(\Rightarrow2x=42-12\) \(\Rightarrow x=6\)
\(\Rightarrow2x=30\) Vậy x = 6
\(\Rightarrow x=15\)
Vậy x = 15
45 + x = 2x
x =45
2 + x - 4 =12
x - 2 = 12
x = 14
10 +x = 5 + 2x
-x = -5
x = 5
42 - 2x = 12
-2x = -30
x = 15
4x + 3x = 70
7x = 70
x = 10
6x - 18 = 0
6x = 18
x = 3
72x : 36 = 2
72x = 72
x = 1
13 +x = 5 +2x
-x = -8
x = 8
học tốt
18x -19 = 21 + 8x
18 x - 8x = 21 + 19
10 x = 40
x =4
g) 18 -4x=-20-6x
-4x + 6x = -20 - 18
2x = -38
x= -19
k, -10 \(x\) - 27 = -7\(x\) + 33
-27 - 33 = -7\(x\) + 10\(x\)
3\(x\) = -60
\(x\) - 20
m, -17\(x\) - 24 = -9\(x\) - 40
-24 + 40 = -9\(x\) + 17\(x\)
8\(x\) = 16
\(x\) = 2
x + 12 =(-5)-x
x + x = -5 - 12
2x = -17
\(x=-\frac{17}{2}\)
x + 5 = 10 - x
x + x = 10 - 5
2x = 5
\(x=\frac{5}{2}\)
12-x=x+1
12 - 1 = x+x
11=2x
x=\(\frac{11}{2}\)
14+4x=3x-20
4x-3x=-20-14
x=-34
a; -2\(x\) - 3.(\(x-17\)) = 34 - 2.( - \(x\) + 25)
- 2\(x\) - 3\(x\) + 51 = 34 + 2\(x\) - 50
2\(x\) + 2\(x\) + 3\(x\) = - 34 + 50 + 51
7\(x\) = 67
\(x\) = 67 : 7
\(x\) = \(\dfrac{67}{7}\)
Vậy \(x\) = \(\dfrac{67}{7}\)
b; 17\(x\) + 3.(- 16\(x\) - 37) = 2\(x\) + 43 - 4\(x\)
17\(x\) - 48\(x\) - 111 = 2\(x\) - 4\(x\) + 43
- 31\(x\) - 2\(x\) + 4\(x\) = 111 + 43
- \(x\) x (31 + 2 - 4) = 154
- \(x\) x (33 - 4) = 154
- \(x\) x 29 = 154
- \(x\) = 154 : (-29)
\(x\) = - \(\dfrac{154}{29}\)
Vậy \(x=-\dfrac{154}{29}\)
`2x + 3x + 1 - 4x + 2 = 36`
`=> (2+3-4) x + 3 = 36`
`=> x + 3 = 36`
`=> x = 36-3`
`=> x = 33`
Tìm x biết. 180-(x_45):2=120